Second Magnetization Peak Effect in a Fe(Se, Te) iron based superconductor. (May 2019) - Galluzzi, A; Buchkov, K; Tomov, V; Nazarova, E; Leo, A; Grimaldi, G; Nigro, A; Pace, S; Polichetti, M
Abstract: The iron based superconductor FeSe0.5 Te0.5 has been investigated by means of DC magnetic measurements as a function of magnetic field (H). By considering the superconducting m(H) hysteresis loops at different temperatures, the sample shows a strong superconducting signal together with the presence of a peak effect that causes an anomalous increase in the field dependence of the critical current density Jc (H). The presence of the peak effect has been studied by means of the Jc (T) obtained at different magnetic fields starting from the Jc (H) curves. The analysis of the Jc (T) curves shows that the peak effect is due to a crossover from a weak pinning regime to a strong pinning regime.